2021
DOI: 10.1084/jem.20202490
|View full text |Cite
|
Sign up to set email alerts
|

Blood stem cell PU.1 upregulation is a consequence of differentiation without fast autoregulation

Abstract: Transcription factors (TFs) regulate cell fates, and their expression must be tightly regulated. Autoregulation is assumed to regulate many TFs’ own expression to control cell fates. Here, we manipulate and quantify the (auto)regulation of PU.1, a TF controlling hematopoietic stem and progenitor cells (HSPCs), and correlate it to their future fates. We generate transgenic mice allowing both inducible activation of PU.1 and noninvasive quantification of endogenous PU.1 protein expression. The quantified HSPC PU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…To test our hypothesis, we treated PU.1-EYFP reporter mice with IL-1β or PBS (hereafter referred to as -IL-1β) daily for 20 days to simulate a chronic inflammatory state. The PU.1-EYFP reporter mouse line harbors EYFP fused to the C-terminus of PU.1 and is knocked into the endogenous PU.1 locus, allowing for prospective isolation of cells based on PU.1 protein levels [ 3 , 7 , 8 , 9 , 15 , 17 ]. Following IL-1β treatment, we verified increased numbers of neutrophils and platelets in the peripheral blood by CBC, and as we previously reported, we noted increased overall numbers of phenotypic HSC-enriched SLAM cells in the BM ( Figure S1A,B ) [ 6 , 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test our hypothesis, we treated PU.1-EYFP reporter mice with IL-1β or PBS (hereafter referred to as -IL-1β) daily for 20 days to simulate a chronic inflammatory state. The PU.1-EYFP reporter mouse line harbors EYFP fused to the C-terminus of PU.1 and is knocked into the endogenous PU.1 locus, allowing for prospective isolation of cells based on PU.1 protein levels [ 3 , 7 , 8 , 9 , 15 , 17 ]. Following IL-1β treatment, we verified increased numbers of neutrophils and platelets in the peripheral blood by CBC, and as we previously reported, we noted increased overall numbers of phenotypic HSC-enriched SLAM cells in the BM ( Figure S1A,B ) [ 6 , 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, increased PU.1 expression following inflammatory stimulation is dynamic. We and others have shown that elevated PU.1 expression is reversible and is not sustained in HSC following the removal of IL-1β or other cytokines [ 3 , 9 ]. Second, the ‘myeloid bias’ phenotype in the setting of transplantation appears closely linked to high levels of HSC activity, and the original characterizations of ‘myeloid-biased’ HSC interpret the elevated myeloid lineage output to be at least in part related to the engraftment of highly potent primitive HSC [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunostaining of VENUS fluorescent protein in myeloid progenitors was performed according to protocols as described 31 , 34 , 39 , 55 . Briefly, different subsets of myeloid progenitors based on VENUS expression were sorted by FACS (BD ARIA III), directly seeded on (10 µg/mL) anti CD43-biotin antibody-coated plastic-bottom 96-well plates (Greiner Bio-one), stored for 30 min at 4 °C and fixed with 4% paraformaldehyde (Sigma Aldrich) for 10 min at RT.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative time-lapse imaging of transcription factor dynamics has provided key insights into gene regulatory network function in single cell organisms and mammalian cell lines [3336]. For example, through observation of PU.1 and GATA1 dynamics in mouse cell lines, Hoppe et al [37] challenged an existing model that early myeloid lineage choice is determined by random fluctuations of these mutually antagonistic transcription factors.…”
Section: Introductionmentioning
confidence: 99%